The pathogenic Yersiniae - advances in the understanding of physiology and virulence - Matthew S. Francis (Frontiers Research Topics, 2014)
For decades, pathogenic Yersinia have served as an inventive model organism for researchers seeking to understand the complexities of bacteria-host cell interactions. In fact, seminal studies on Yersinia virulence mechanisms contributed to the emergence and recognition of the research field - cellular microbiology. Researching Yersinia infection biology continues to identify and define fascinating virulence and survival mechanisms that advance and expand existing perceptions of bacterial-host encounters. This also includes research that defines how the pathogenic Yersiniae respond to diverse physicochemical stimuli to spatially and temporally control this armory of customized virulence and survival factors. Yet additional research demonstrates how the application of powerful whole genomic-based methodologies can open new frontiers that further facilitate understanding of bacterial evolution and pathogenicity. This Research Topic is therefore focused on presenting and summarizing new developments in Yersinia patho-physiology through highlighting cutting- edge studies on the Yersinia-host cell interaction and the network of regulatory control mechanisms that define this outcome.